2019
DOI: 10.1037/dev0000797
|View full text |Cite
|
Sign up to set email alerts
|

Malleability of whole-number and fraction biases in decimal comparison.

Abstract: Children and adults often have difficulties comparing decimal magnitudes. Although individuals attempt to reconcile decimals with prior whole-number and fraction knowledge, conceptual and procedural differences between decimals and prior knowledge of whole numbers and fractions can lead to incorrect strategies. The dynamic strategy choice account has proposed that saliency, recency, prior knowledge, and other factors contribute to strategy use when reasoning about decimals. We experimentally tested this theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…Among whole numbers, more digits always indicates a larger number, making it harder to determine the larger of 0.9 vs. 0.27 relative to pairs where the larger number also has more digits, such as 0.2 vs. 0.87. This string length congruity effect (Huber, Klein, Willmes, Nuerk, & Moeller, 2014) is found in children (Avgerinou & Tolmie, 2019;Ren & Gunderson, 2019) and adults (Varma & Karl, 2013) and even induces priming effects on subsequent processing in children and adolescents (Roell, Viarouge, Houde, & Borst, 2017. Other effects have also been investigated in decimal comparison (Huber et al, 2014;Varma & Karl, 2013), including the unit decade compatibility effect (slower reaction times when the tenths and hundredths digit conflicts, e.g., 0.19 vs. 0.86) and the zero facilitation effect (faster reaction for problems involving zero, see Appendix A).…”
Section: Role Of Inhibitory Control In Rational Number Understandingmentioning
confidence: 82%
See 1 more Smart Citation
“…Among whole numbers, more digits always indicates a larger number, making it harder to determine the larger of 0.9 vs. 0.27 relative to pairs where the larger number also has more digits, such as 0.2 vs. 0.87. This string length congruity effect (Huber, Klein, Willmes, Nuerk, & Moeller, 2014) is found in children (Avgerinou & Tolmie, 2019;Ren & Gunderson, 2019) and adults (Varma & Karl, 2013) and even induces priming effects on subsequent processing in children and adolescents (Roell, Viarouge, Houde, & Borst, 2017. Other effects have also been investigated in decimal comparison (Huber et al, 2014;Varma & Karl, 2013), including the unit decade compatibility effect (slower reaction times when the tenths and hundredths digit conflicts, e.g., 0.19 vs. 0.86) and the zero facilitation effect (faster reaction for problems involving zero, see Appendix A).…”
Section: Role Of Inhibitory Control In Rational Number Understandingmentioning
confidence: 82%
“…Thus, abstracting a single index of fraction understanding from comparison tasks may be challenging without considering strategy information (Braithwaite, Pyke, & Siegler, 2017). Decimal comparison is not without strategy variation (Ren & Gunderson, 2019;Resnick et al, 1989). A further complication is that inconsistent decimals comparison involves interference from both numerical values of stimuli and also their physical length, as demonstrated by recent negative priming studies (Roell, Viarouge, Hilscher, Houde, & Borst, 2019;,.…”
Section: Decimal Comparison and Overall Math Skillsmentioning
confidence: 99%
“…A robust phenomenon in studies on decimal comparison is lower accuracy and slower response times on comparisons that are incongruent with whole number knowledge (e.g., 0.9 vs. 0.23 because 23 > 9 but 0.23 < 0.9) (Avgerinou & Tolmie, 2020; Coulanges et al, 2021; Huber et al, 2014; Ren & Gunderson, 2019; Varma & Karl, 2013). Two explanations have been posited for this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Similar priming phenomena were observed in tasks with symbolic formats. For example, Ren and Gunderson (2019) demonstrated that children primed with whole number comparison (or a flanker control task) prior to decimal comparison performed substantially worse on trials with incongruent rather than congruent whole number components (e.g., worse performance on .9 vs. .23 than .2 vs. .93). These differences between congruent and incongruent trials were not present when participants were primed with decimals (or fractions) before the decimal trials.…”
Section: Priming Effects In Rational Numbersmentioning
confidence: 99%
“…A limitation of the current work is that we do not have a non-numerical priming condition to act as a control for the priming effects. For example, Ren and Gunderson (2019) found that the non-numerical control priming condition (i.e., the flanker task) had similar effects to the whole number priming condition, namely, worse performance on a decimal comparison task relative to a fraction priming condition. This pattern of results suggests that among children, the default state is one where whole number knowledge interferes.…”
Section: Decimal Magnitude Representation Is Impacted By String Lengt...mentioning
confidence: 99%